Molecular dynamics simulations of AOT-water/formamide reverse micelles: Structural and dynamical properties - Pomata, Matias Hernan Hugo (2009)
We present results from molecular dynamics simulations performed on reverse micelles immersed in cyclohexane. Three different inner polar phases are considered: water (W), formamide (FM), and an equimolar mixture of the two solvents. In all cases, the surfactant was sodium bis(2-ethylhexyl) sulfosuccinate (usually known as AOT). The initial radii of the micelles were R∼15 Å, while the corresponding polar solvent-to-surfactant molar ratios were intermediate between w0 =4.3 for FM and w0 =7 for W. The resulting overall shapes of the micelles resemble distorted ellipsoids, with average eccentricities of the order of ∼0.75. Moreover, the pattern of the surfactant layer separating the inner pool from the non-polar phase looks highly irregular, with a roughness characterized by length scales comparable to the micelle radii. Solvent dipole orientation polarization along radial directions exhibit steady growths as one moves from central positions toward head group locations. Local density correlations within the micelles indicate preferential solvation of sodium ionic species by water, in contrast to the behavior found in bulk equimolar mixtures. Still, a sizable fraction of ∼90% of Na+ remains associated with the head groups. Compared to bulk results, the translational and rotational modes of the confined solvents exhibit important retardations, most notably those operated in rotational motions where the characteristic time scales may be up to 50 times larger. Modifications of the intramolecular connectivity expressed in terms of the average number of hydrogen bonds and their lifetimes are also discussed.